2018
DOI: 10.1016/j.ajo.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Community Screening on the Demographic Makeup and Clinical Severity of Glaucoma Patients Receiving Care in Urban China

Abstract: Glaucoma patients detected through community screening had significantly milder damage, and were more likely to include underserved groups (women, elderly) than those newly diagnosed in a clinic in this setting. Comparison with population studies suggests that cases of glaucoma with IOP < 21 mm Hg are severely underascertained in China, a situation that may be improved by screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 44 publications
10
32
2
1
Order By: Relevance
“…Consistent with our previous finding in this setting that those detected with glaucoma through outreach screening had significantly milder damage than those diagnosed in clinic. 36 Early detection through screening and appropriate intervention may delay or prevent the progression of the disease and lead to improved quality of life for glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous finding in this setting that those detected with glaucoma through outreach screening had significantly milder damage than those diagnosed in clinic. 36 Early detection through screening and appropriate intervention may delay or prevent the progression of the disease and lead to improved quality of life for glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because of insufficient data, it was inappropriate to provide separate prevalence estimates for bilateral POAG blindness for rural and urban areas and so a single estimate was provided for both. We used data from a glaucoma screening programme of 27 144 participants in Wenzhou, China, 6 that was carried out by a coauthor (YL) between March, 2014, and September, 2015, to estimate the propor tion of patients with POAG with mild disease as 36•8%, moderate disease as 35•9%, and severe disease as 27•3%.…”
Section: Glaucoma Prevalencementioning
confidence: 99%
“…5 Among those who are diagnosed, glaucoma has already caused severe damage in the majority. 6 However, several studies have reported that populationbased glaucoma screening programmes are not costeffective in high income countries such as the UK 7,8 and Finland. 9 We believe that glaucoma screening might be cost effective in a Chinese setting for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we chose the same diagnostic criteria used in other studies worldwide as well as in the local area to obtain comparable and reliable results. For example, the definitions of glaucoma used in the YODI were also used in the Wenzhou Glaucoma Screening Program [75]. We also implemented the same protocol of sample collection as the other metabolomics study [43] for clarity and consistency.…”
Section: Discussionmentioning
confidence: 99%
“…5. Glaucoma suspect[75]: A glaucoma suspect was considered if any of the following characteristics were observed in either eye: 1) IOP > 21 mmHg; 2) Optic disc margin hemorrhage on the fundus disc-centered photography; 3) Cup-disc ratio (CDR) ≥ 0.65, CDR asymmetry ≥ 0.2 or neural rim tissue ≤ 0.1; 4) Diffused or localized retinal nerve fiber layer defect on fundus photography.…”
mentioning
confidence: 99%